RoboEthics in COVID-19: A Case Study in Dentistry - Maddahi, Yaser; Kalvandi, Maryam; Langman, Sofya; Capicotto, Nicole; Zareinia, Kourosh (Frontiers in Robotics and AI, 2021)
The COVID-19 pandemic has caused dramatic effects on the healthcare system, businesses, and education. In many countries businesses were shut down, universities and schools had to cancel in-person classes, and many workers had to work remotely and socially distance in order to prevent the spread of the virus. These measures opened the door for technologies such as robotics and artificial intelligence to play an important role in minimizing the negative effects of such closures. There have been many efforts in the design and development of robotic systems for applications such as disinfection and elder care. Healthcare education has seen a lot of potential in simulation robots, which offer valuable opportunities for remote learning during the pandemic. However, there are ethical considerations that need to be deliberated in the design and development of such systems. In this paper, we discuss the principles of roboethics and how these can be applied in the new era of COVID-19. We focus on identifying most relevant ethical principles and apply them to a case study in dentistry education. DenTeach was developed as a portable device that uses sensors and computer simulation to make dental education more efficient. DenTeach makes remote instruction possible by allowing students to learn and practice dental procedures from home. We evaluate DenTeach on the principles of data, common good, and safety, and highlight the importance of roboethics in Canada. Principles identified in this paper can inform researchers and educational institutions considering implementing robots in their curriculum.